Demographics and clinical characteristics of carbon monoxide poisoning for patients attending in the emergency department at a tertiary hospital in Riyadh, Saudi Arabia - Alharthy, Nesrin; Alanazi, Aljohara; Almoqaytib, Alreem; Alharbi, Bedour; Alshaibani, Rakad; Albuniyan, Jawaher; Alshibani, Abdullah (International journal of emergency medicine, 2024)
Background Carbon Monoxide (CO) is one of the most common environmental causes of acute intoxication globally. It can lead to the development of Delayed Neuropsychiatric Sequelae (DNS) which may develop in 2-40 days after remission of acute CO poisoning. DNS is defined by recurrent-transient neurological, cognitive, or psychological manifestations. This study was intended to describe the demographics and characteristics of CO poisoning patients attending at the Emergency Department (ED) and assess the association between CO intoxication and the development of DNS in a tertiary hospital, Riyadh, Saudi Arabia. Methods A retrospective descriptive cross-sectional study was conducted in subjects who were diagnosed with CO poisoning and attended to the ED at King Abdulaziz Medical City (KAMC) and King Abdullah Specialist Children’s Hospital (KASCH) in Riyadh during the period from January 2016 to December 2021. Patient demographics, vitals, diagnostic tests, and oxygen therapy at initial presentation were documented. Patient medical records were reviewed at 2-40 days following CO poisoning for development of DNS. Ethical approval was obtained from King Abdullah International Medical Research Center (KAIMRC). Results A total of 85 patients were diagnosed with CO poisoning and met the study inclusion criteria. Of those, 76% were adults with an average age of 32.36 (SD ± 15.20) and 51% were male adults. Five (6%) of the 85 patients developed DNS. Common symptoms included dizziness, nausea, and decreased visual acuity in 40% of the cases. The development of DNS manifestations was most likely (80%) to occur at 2 to 10 days after the initial incident. Inferential statistics showed that BMI ( p -value = 0.021) and age group (p-value = 0.029) were significantly associated with COHb level, which was not the case for gender and the presence of clinical manifestation. Furthermore, Gender was significantly associated with the development of DNS (20% male vs. 80% female, p = 0.050). Conclusions The findings of this study are consistent with previous published studies showing low proportions of patients who were exposed to CO poisoning at risk of developing DNS. Further larger-scale multicenter studies are needed to assess the factors associated with the development of DNS for patients with CO poisoning.